2021
DOI: 10.1007/s11325-021-02384-2
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review of systematic reviews and meta-analyses of observational investigations of obstructive sleep apnea and health outcomes

Abstract: Purpose The previous analysis of systematic reviews and meta-analyses have illustrated that obstructive sleep apnea (OSA) is correlated with multiple health outcomes. In the present research, our main aim was to execute an umbrella review to assess the available evidence for the associations between OSA and health outcomes. Methods Herein, a meta-analysis of previous observational investigations that have reported associations between OSA and health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 93 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Other umbrella reviews which have used this tool have also found similar results; the verdicts were all either low or critically low [57,58]. We briefly explore the implications of this in the limitations.…”
Section: Discussionmentioning
confidence: 65%
“…Other umbrella reviews which have used this tool have also found similar results; the verdicts were all either low or critically low [57,58]. We briefly explore the implications of this in the limitations.…”
Section: Discussionmentioning
confidence: 65%
“…Our results are in line with previous studies that failed to demonstrate a link between the occurrence of OSA and more severe neuropsychiatric symptoms [64,65], whereas the absence of a relationship with cognition seems to be in contrast with previous results in both PD [2] and non-PD populations [66][67][68]. It should be noted that the cross-sectional methodology we employed in the present meta-analysis might have affected this result, because a recent study performed by Meira et al [32] Although OSA does not appear to affect patients' QoL, the possible detrimental effect of intermittent hypoxia on the brain, which is already vulnerable to PD degenerative processes, should not be underestimated due to its prevalence and adverse consequences [2,69].…”
Section: Discussionmentioning
confidence: 84%
“…Although OSA does not appear to affect patients' QoL, the possible detrimental effect of intermittent hypoxia on the brain, which is already vulnerable to PD degenerative processes, should not be underestimated due to its prevalence and adverse consequences [2, 69].…”
Section: Discussionmentioning
confidence: 99%
“…The platform ranks the quality of a meta-analysis as critically low, low, moderate and high, based upon 16 pre-determined parameters. Regarding robustness for epidemiologic proof from each medical end-point, significant correlations (P < 0.05) were rated as high, moderate, or weak proof, in line with a grading exercise which was previously adopted within multiple research niches (23)(24)(25). The above evaluation process was independently completed by WQ and GJ.…”
Section: Discussionmentioning
confidence: 97%